2022
DOI: 10.1002/jssc.202101014
|View full text |Cite
|
Sign up to set email alerts
|

Screening the bioactive compound fromCoptis chinensisinflorescence by immobilized peroxisome proliferator‐activated receptor‐gamma

Abstract: Coptis chinensis inflorescence is a by‐product of Coptis chinensis Franch and riches in alkaloids. We screened the bioactive compounds in the by‐product through an immobilized peroxisome proliferator‐activated receptor gamma. The receptor was covalently immobilized on the macroporous silica gel through amino groups to generate the affinity stationary phase and was applied for screening. Berberine, palmatine, and jatrorrhizine were identified as the retained components of the herb on the affinity column. We eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Research studies conducted by Sun and Hou also confirmed that PPAR-γ is the target of PAL. They immobilized PPAR-γ to screen the bioactive compounds fromCoptis chinensis inflorescence, and identified PAL as the bioactive compounds targeting PPARγthat can specifically bind to PPAR-γ [41,42]. In this study, we further analyzed the potential binding sites of PAL and PPAR-γ using molecular docking analysis, the results showed that The 325THR in PPAR-γ interact with PAL by forming a hydrogen bond.…”
Section: Discussionmentioning
confidence: 92%
“…Research studies conducted by Sun and Hou also confirmed that PPAR-γ is the target of PAL. They immobilized PPAR-γ to screen the bioactive compounds fromCoptis chinensis inflorescence, and identified PAL as the bioactive compounds targeting PPARγthat can specifically bind to PPAR-γ [41,42]. In this study, we further analyzed the potential binding sites of PAL and PPAR-γ using molecular docking analysis, the results showed that The 325THR in PPAR-γ interact with PAL by forming a hydrogen bond.…”
Section: Discussionmentioning
confidence: 92%